NON-INVASIVE VENTILATION IN MND PATIENTS IN WEST OF SCOTLAND. Issue 10 (9th September 2014) - Law, Sheonagh; Murphy, Grace; Clarke, Alison; Ferguson, Carole; Gorrie, George; Davidson, Scott
Abstract : Introduction: Motor Neurone Disease (MND) results in respiratory muscle weakness and respiratory failure (RF) with significant consequences on quality of life and survival, both of which can be improved with Non-invasive Ventilation (NIV). 1 2 In the West of Scotland (WoS), an average 81 patients are diagnosed with MND per annum. Aim: to evaluate our current practice in the WoS Long-Term Ventilation Unit (WoSLTVU), comparing it with our pre-NICE guideline data. Methods: Retrospective audit of referrals from 2010–2013. Data collected from electronic medical records: presence of RF, age, sex, length of survival from diagnosis, and NIV use. Results: Referrals: 99 from 2010–2013 vs. 38 from 2007–2010 and only 12 from 1999–2002. Of the 99, 35 had RF at referral and 14 developed RF during follow-up. 89% patients referred from Neurology. 88% patients with RF elected to be treated with NIV. Length of survival (mean±SEM) in the RF-NIV group was 536±48 days vs. 206±128 in RF-non-NIV-group (p=0.033) and non-RF group: 532±65 days. Conclusions: Referrals to WoSLTVU increased significantly following NICE guideline publication. NIV lengthened survival by 11 months. This highlights the importance of respiratory support and need for early engagement with respiratory services for the multidisciplinary care of MND patients.